Mentalization, Attachment and Quality of Emerging Adults' Relationships - EL Ghannam, Mai K. (AUC Knowledge Fountain, 2022)
The emerging adulthood phase has specific characteristics related to identity formation and raising the desire for autonomy and independence. One of the exciting functioning abilities at this life stage is their interpersonal functioning abilities. The emerging adults' quality of relationships can be better understood by understanding their attachment styles and mentalization capacity. Thus, this study aimed at understanding the correlation between emerging adults' different attachment styles, mentalization capacity, and their level of interpersonal functioning. A total of 77 emerging adults participated in the study by answering questions related to their mentalization capacity, attachment style, and interpersonal functioning level. The results showed a significant correlation between mentalization capacity and bi-directional communication styles. It also showed high significance between emerging adults' attachment styles and their interpersonal functioning level. The finding shed light on the relevance of emerging adults' attachment styles and their capability to experience and express their emotions. In addition to their ability to build disclosure about themselves, share experiences, and form close interpersonal relationships.